Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Sektor Perbankan Di Indonesia: Peran Moderasi Kepemilikan Manajerial - Ni Putu Dewi Maharani; Ikhsan Budi Riharjo; David Efendi (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This study aims to analyze the effect of profitability on company value, the effect of company size on company value, the effect of managerial ownership moderation on the relationship between profitability and company value, and the effect of managerial ownership moderation on the relationship between company size and company value. This study uses a quantitative method with purposive sampling, involving 36 samples from 47 banking companies listed on the Indonesia Stock Exchange. A total of 252 observations were analyzed using moderation regression through SPSS. The results of this study show that profitability has a positive effect on the company's value. The regression results show that profitability has a positive and significant effect on the company's value. Company Size has a positive effect on the company's value, because the company size has no significant effect. Managerial ownership moderates the relationship between Profitability and company value, in part, with a negative influence